The Effect Of Fear Of Missing Out (FOMO) On The Psychological Wellbeing Of Social Media Users For Students In Medan City - Tampubolon, Santa Maria; Brahmana, Karina Merriem Beru (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to evaluate the influence of Fear of Missing Out (FOMO) on the psychological well-being of social media users among students in Medan City. The sampling technique in this study is by using one of the non-probability sampling techniques, namely purposive sampling, which is a sampling technique based on consideration of the criteria of the research subjects according to what the researcher wants to study and draw conclusions. Based on the results of a simple linear regression analysis, it can be concluded that Fear of Missing Out (FOMO) does not have a significant influence on psychological well-being (PWB) in students. This is also shown by the R value of 0.076 which indicates a very small influence between the two variables. The R Square value of 0.006 indicates that only 0.6% of the variability in psychological well-being can be explained by FoMO, while the rest is influenced by other factors outside the model. The Adjusted R Square value of -0.001 also indicates that this regression model cannot be generalized and has very low predictive ability. In addition, the ANOVA test results show a calculated F value of 0.850 with a significance (p) of 0.358 (> 0.05), which means that the regression model is not statistically significant. Thus, the null hypothesis (H₀ ) is accepted and the alternative hypothesis (H₁ ) is rejected. This means that there is no significant influence between FoMO on psychological well-being in students in this study.